DNA Microarray Analysis of Submandibular Glands in IgG4-Related Disease Indicates a Role for MARCO and Other Innate Immune-Related Proteins. Issue 7 (February 2016) - Ohta, Miho; Moriyama, Masafumi; Maehara, Takashi; Gion, Yuka; Furukawa, Sachiko; Tanaka, Akihiko; Hayashida, Jun-Nosuke; Yamauchi, Masaki; Ishiguro, Noriko; Mikami, Yurie; Tsuboi, Hiroto; Iizuka-Koga, Mana; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: IgG4-related disease (IgG4-RD) is a novel systemic disease entity characterized by elevated serum IgG4 and tissue infiltration of IgG4-positive plasma cells accompanied by severe fibrosis. Although recent studies demonstrated that innate immune cells including monocytes and macrophages might promote local fibrosis and IgG4 production, the pathological mechanism remains unclear. In this study, we sought to identify the disease-associated genes, especially innate immune molecules. Gene expression was analyzed by DNA microarray in submandibular glands (SMGs) from patients with IgG4-RD (n = 5), chronic sialoadenitis (CS) (n = 3), and controls (n = 3). Differentially expressed genes (DEGs) were validated by real-time polymerase chain reaction (PCR) and immunohistochemical staining in IgG4-RD (n = 18), CS (n = 4), Sjögren syndrome (n = 11), and controls (n = 10). Gene expression patterns in the 3 groups were quite different from each other by the pvclust method and principal components analysis. In IgG4-RD, 1028 upregulated genes and 692 downregulated genes were identified as DEGs ( P < 0.05). Gene Ontology (GO) term analysis indicated that the upregulated DEGs in IgG4-RD encoded proteins involved in T/B cell activation and chemotaxis. PCR validated significantly higher expression of macrophage receptor with collagenous structure (MARCO), a pattern-recognition receptor, in IgG4-RD compared with the other groups ( P < 0.01). Immunohistochemical analysis confirmed that the expression pattern of MARCO was similar to that of the M2 macrophage marker CD163. MARCO was identified as a disease-associated molecule in IgG4-RD by DNA microarray. Moreover, M2 macrophages might contribute to the initiation of IgG4-RD via MARCO.